2012
DOI: 10.1177/0956797611429134
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodevelopmental Basis of Math Anxiety

Abstract: Math anxiety is a negative emotional reaction to situations involving mathematical problem solving. Math anxiety has a detrimental impact on an individual’s long-term professional success, but its neurodevelopmental origins are unknown. In a functional MRI study on 7- to 9-year-old children, we showed that math anxiety was associated with hyperactivity in right amygdala regions that are important for processing negative emotions. In addition, we found that math anxiety was associated with reduced activity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
217
5
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(265 citation statements)
references
References 36 publications
18
217
5
15
Order By: Relevance
“…Lyons and Beilock (2010) found that even thoughts of doing math elicited a negative emotional response from math anxious students. Neuroimaging data show increased activity in regions associated with processing negative emotions (such as the amygdala) when performing arithmetic tasks in high math anxiety participants (Young, Wu, & Menon, 2012) Hembree (1990) conducted a meta-analysis of the effects of math anxiety. The studies reviewed demonstrate that high math anxiety individuals enrol in fewer math courses and earn lower grades when they do study math.…”
Section: Interactivity Defuses the Impact Of Math Anxiety In Primary mentioning
confidence: 99%
“…Lyons and Beilock (2010) found that even thoughts of doing math elicited a negative emotional response from math anxious students. Neuroimaging data show increased activity in regions associated with processing negative emotions (such as the amygdala) when performing arithmetic tasks in high math anxiety participants (Young, Wu, & Menon, 2012) Hembree (1990) conducted a meta-analysis of the effects of math anxiety. The studies reviewed demonstrate that high math anxiety individuals enrol in fewer math courses and earn lower grades when they do study math.…”
Section: Interactivity Defuses the Impact Of Math Anxiety In Primary mentioning
confidence: 99%
“…One of the milestone studies (Lyons & Beilock, 2012b) in MA research found that math anxious individuals activate more regions related to pain perception during the anticipation of mathematical processing, like the dorsal part of the posterior insula and mid-cingulate cortex. Moreover, Young, Wu, & Menon (2012) reported that MA activates regions (right amygdala) that regulate negative emotions, while they have also reported that MA inhibits activation in brain regions associated with mathematical reasoning, such as the posterior parietal and dorsolateral prefrontal cortex. Regarding the impact of MA in the brain's electrophysiology, Suárez-Pellicioni, Núñez-Peña, & Colomé (2013) revealed the relationship between the arithmetic split effect (Ashcraft & Battaglia, 1978) and the P600/P3b component which was more enhanced and delayed during MA state.…”
Section: Introductionmentioning
confidence: 99%
“…Bishop (2007) reviewed numerous neuroimaging studies to show that these biases towards threatening information are linked to hyperactivity in the amygdala (a part of the brain thought to be involved in processing negative emotions) and reduced activation of the prefrontal cortex (a part of the brain involved in emotion regulation). Young, Wu, and Menon (2012), for example found that activation in the amygdala and deactivation in parts of the prefrontal cortex associated with the regulation of emotion (the ventromedial prefrontal cortex) were greater among seven-to nine-year-old children with high MA than among children with low MA. Interestingly, Young and colleagues (2012) also found that children in the high MA group had greater connectivity between the amygdala and the ventromedial prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%